A trust betrayed : the untold story of Camp Lejeune and the poisoning of generations of Marines and their families - Magner, Mike (Merloyd Lawrence Book., 2014)
A gripping exposé of the most lethal drinking water contamination in US history and the 30-year denial by military authorities.